Analisis Kontribusi Institusi Pendidikan Tinggi Islam dalam Perkembangan Bank Syariah di Kota Medan - Imsar; Syahriza , Rahmi; Nasution, Mikayani (Regress: Journal of Economics & Management, 2022)
This article aims to analyze the contribution of Islamic higher education institutions in the development of Islamic banks in Medan City. The development of Islamic banks over the past five years can be seen in the financial reports which have increased but not accompanied by an increase in the market share of Islamic banks and are still lagging behind other Muslim-majority countries. Islamic higher education institutions which are educational institutions required to contribute to the development of Islamic banks. The research method used is descriptive qualitative. The results of the study show that Islamic tertiary institutions, namely UINSU and UMSU, have contributed to the development of Islamic banks in the city of Medan by: increasing the number of customers, providing human resources and increasing cooperation networks, these contributions show that UINSU and UMSU have made various efforts to help development of sharia banks in the form of cooperation, namely: Payment of student tuition fees, payment of lecturer salaries and allowances, apprenticeships for students and opening of mini-banks within universities.